The Latest Occurrence of Stephanorhinus hundsheimensis (Rhinocerotidae) in Europe: The Skeletons from the Cova del Rinoceront Site (Castelldefels, Barcelona) - David García-Fernández; Esperanza Cerdeño; Montserrat Sanz; Joan Daura (Quaternary, 2023)
New rhino remains recovered from Cova del Rinoceront (Castelldefels, Barcelona) confirm the presence of Stephanorhinus hundsheimensis (Toula, 1902) at the site and the taxon’s persistence until the late Middle–early Upper Pleistocene in Europe, that is, its latest documented occurrence. The three individuals recovered from the site are compared with specimens of other Pleistocene species, including those of S. hemitoechus, S. kirchbergensis and Coelodonta antiquitatis, but their anatomical characteristics (a long skull, moderate occipital elevation, partial nasal septum, and slender zygomatic arch) do not coincide with the latter’s documented features. Certain similarities are found with the most frequently occurring rhinocerotid at that time in the Iberian Peninsula, S. hemitoechus, but the cranial features of the latter differ. The anatomical characteristics of the Cova del Rinoceront individuals coincide most closely with those of S. hundsheimensis (i.e., a high occipital face, with rounded proximolateral angles and oblique lateral borders, as well as the frontoparietal angle, and facial development). Despite the marked overlaps in the general measurements of S. hundsheimensis and S. hemitoechus, many (cranial and postcranial) dimensions of the Cova del Rinoceront individuals coincide more closely with those of the former, although some bone proportions are more similar to those of the latter specimens. Therefore, S. kirchbergensis and C. antiquitatis can be discarded as they tend to be larger, more robust species.